2009
DOI: 10.1016/j.canlet.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Circulating melatonin and the risk of breast and endometrial cancer in women

Abstract: Several decades of observational data have accumulated to implicate a potential role for melatonin in cancer prevention. Experimental studies suggest that the antineoplastic action of melatonin arises through many different mechanisms, including melatonin's antioxidant, antimitotic, and antiangiogenic activity, as well as its ability to modulate the immune system and alter fat metabolism. Melatonin interacts with membrane and nuclear receptors, and may be linked to the regulation of tumor growth. Of particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 76 publications
(67 reference statements)
2
97
1
Order By: Relevance
“…Artificial light at night can modify the diurnal melatonin production. It has been proposed that suppressed melatonin production may lead to an increased cancer risk, but further research is needed to fully establish the mechanistic pathways leading to circadian disruption and cancer (24)(25)(26)(27)(28). However, cancer as a systemic disease or the treatment thereof can interfere with biomarker levels, making case-control studies less suitable for the determination of melatonin and other biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial light at night can modify the diurnal melatonin production. It has been proposed that suppressed melatonin production may lead to an increased cancer risk, but further research is needed to fully establish the mechanistic pathways leading to circadian disruption and cancer (24)(25)(26)(27)(28). However, cancer as a systemic disease or the treatment thereof can interfere with biomarker levels, making case-control studies less suitable for the determination of melatonin and other biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggest that lowered melatonin level due to exposure to night light contributes toward breast cancer development and drug resistance. Melatonin is thought to exert its oncostatic effect through multiple mechanisms including antimitosis, anti-angiogenesis, anti-oxidation and regulation of immune response (Viswanathan & Schernhammer 2009). The oncostatic effect of melatonin in breast cancer is thought be mediated through its anti-estrogenic actions as well as its role in regulating the activity of aromatases, the enzymes responsible for the local biosynthesis of estrogens from androgens (Cos et al 2006).…”
Section: Nuclear Receptors In Breast Cancermentioning
confidence: 99%
“…96 On the other hand, both case-control and prospective cohort studies have consistently linked night shift work with breast cancer risk and, more recently, endometrial cancer, both of which are highly sensitive to estrogens. 97 Despite the proven effects of estrogens on sleep regulation, women starting HRT often also take progesterone to protect themselves against the harmful endometrial effects of estrogens. Studies of progesterone's effects on sleep have yielded variable results.…”
Section: Estrogens -Progesteronementioning
confidence: 99%
“…Although the evidence for an association between sleep duration and breast cancer risk is unclear, overall there is increasing support for a potentially important link between melatonin and breast cancer risk. 97 A possible link between diminished secretion of melatonin and increased exposure to light during night-time has been suggested. 116 Ultimately, genome-wide association studies [117][118][119] have shown that variation in the melatonin receptor 1B (MTNR1B)-a receptor known to be linked to the circadian rhythm of sleep-is associated with insulin and glucose concentrations as well as with the risk of type 2 diabetes (T2D).…”
Section: Melatoninmentioning
confidence: 99%